Blockchain Technology in Pharmaceutical Supply Chains: A Feasibility Assessment in Nepal (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2026)
Substandard and falsified medicines remain a major public health concern in low- and middle-income countries (LMICs), with Nepal facing significant challenges due to its import-dependent pharmaceutical supply chain and limited traceability mechanisms. Nepal recorded hundreds of drug recalls over the past decade, while studies indicate that a notable proportion of essential medicines fail quality standards. This study presents the first Nepal-specific blockchain feasibility assessment, examining the viability of adopting blockchain technology to improve transparency and traceability in Nepal's pharmaceutical supply chain. Drawing on secondary data analysis and a narrative literature review of 28 indexed sources published between 2020 and 2025, consulted across databases including PubMed, Scopus, Google Scholar, and institutional repositories (WHO, ITU, DDA, MTaPS), blockchain feasibility was evaluated across five dimensions: technical suitability, digital infrastructure readiness, regulatory and governance environment, economic feasibility, and stakeholder ecosystem. The findings indicate that blockchain is technically well-suited (rated High) to Nepal's supply chain challenges, while digital infrastructure readiness is Moderate. Regulatory and governance capacity, economic feasibility, and stakeholder ecosystem readiness are currently rated Low to Low-Moderate, representing the primary barriers to implementation. The study concludes that blockchain adoption should follow a phased approach supported by regulatory reform, capacity building, and pilot projects, and proposes a practical implementation roadmap for Nepal.